2017
DOI: 10.4274/tdd.3320
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Role of Neurotrophins in the Psoriasis and Metabolic Syndrome Relationship

Abstract: ÖzAmaç: Psoriasis hastalarında ve sağlıklı kontrollerde serum ve deri örneklerinde beyin türevli nörotrofik faktör (BDNF), sinir büyüme faktörü (NGF), tümör nekroz faktör-α (TNF) ve interlökin-6 (IL) düzeylerini belirleyerek metabolik sendrom (MetS) ve psoriasis ilişkisinde nörotrofinlerin yerini değerlendirmeyi amaçladık. Yöntemler: Serum BDNF, NGF, TNF-α ve IL-6 düzeyleri ticari hazır ELISA kitleri ile değerlendirildi. BDNF, NGF, TNF-α ve IL-6 antikorları ile BDNF, NGF, TNF-α ve IL-6'nın derideki ekspresyon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Study characteristics are presented in Table 1 . A total of 61.9% of the studies were from Asian countries [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ], and 52.4% were case-control studies [ 29 , 31 , 33 , 37 , 38 , 41 , 42 , 43 , 44 , 45 , 46 ] with a total of 4286 participants. Eight studies matched participants with age and sex [ 31 , 33 , 34 , 37 , 38 , 42 , 43 , 44 ], three studies matched for BMI [ 35 , 41 , 45 ] and only one study matched for ethnicity [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Study characteristics are presented in Table 1 . A total of 61.9% of the studies were from Asian countries [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ], and 52.4% were case-control studies [ 29 , 31 , 33 , 37 , 38 , 41 , 42 , 43 , 44 , 45 , 46 ] with a total of 4286 participants. Eight studies matched participants with age and sex [ 31 , 33 , 34 , 37 , 38 , 42 , 43 , 44 ], three studies matched for BMI [ 35 , 41 , 45 ] and only one study matched for ethnicity [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies matched participants with age and sex [ 31 , 33 , 34 , 37 , 38 , 42 , 43 , 44 ], three studies matched for BMI [ 35 , 41 , 45 ] and only one study matched for ethnicity [ 45 ]. A total of 71.4% of studies had a higher number of males compared to females [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 37 , 38 , 40 , 41 , 44 , 46 , 47 ]. In total, 52.4% of patients with psoriasis were between 40 and 50 years old [ 30 , 31 , 32 , 35 , 36 , 38 , 39 , 41 , 44 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding psoriasis, BDNF was found to be crucial in the maintenance of normal keratinocyte apoptosis and epidermal homeostasis [ 63 ], while p75NTR protein was found to be absent in lesional psoriasis skin. Regarding its serum levels as well as its staining intensities, significantly lower levels were detected in both the epidermis and the dermis of psoriatic patients compared to the control group; however, no difference was observed between the psoriasis patients with and without MetS [ 63 , 64 , 65 ]. Interestingly, in assessing the polymorphism rs6265 in the BDNF gene, its combined effect with higher BMI was found to increase the risk and clinical severity of psoriasis in the Chinese Han population [ 66 ]; nevertheless, as shown in both this and our previous [ 21 ] studies, we found no significant results in the case of rs6265 in our psoriasis cohort.…”
Section: Discussionmentioning
confidence: 99%